Pre-paid domestic gas metering system in Bangladesh: a case study of Titas Gas Transmission and Distribution Company Limited - Kawser, Muhammad Abul (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.